THE IMPACT OF CHANGE MANAGEMENT ON EMPLOYEE PERFORMANCE, JOB SATISFACTION AND ENGAGEMENT: EVIDENCE FROM THE PRIVATE BANKING SECTOR IN SINDH, PAKISTAN - Abdul Jaleel Mahesar; Jawed Ahmed Chandio (Policy Research Journal, 2025)
In this study, the private banking industry in Sindh Province, Pakistan's, employee performance, job satisfaction, and employee engagement were examined in connection to change management strategies. A closed-ended questionnaire survey was used to obtain data from 280 executive workers using a quantitative research methodology. A suitable sampling procedure was employed to approach the respondents. The dynamics of these associations were investigated through the use of Smart PLS software and Structural Equation Modelling (SEM) approach. The results show that change management techniques improve employee engagement as well as job satisfaction while having a favorable and substantial effect on employee performance. According to the findings, change management strategies that are successfully put into practice may create a work atmosphere where staff members feel encouraged, supported, and better prepared to adjust to changes within the company. The study suggests that banking authorities establish an effective change management framework in order to improve employee performance by focusing on the elements that lead to successful change efforts, based on these findings. The study emphasises how crucial it is to mitigate change management's negative consequences in order to guarantee smooth transitions and better results for employees and businesses in the private banking industry.